2006
DOI: 10.1098/rstb.2006.1889
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of connections underlying locomotor recovery after central and/or peripheral lesions in the adult mammals

Abstract: This review discusses some aspects of plasticity of connections after spinal injury in adult animal models as a basis for functional recovery of locomotion. After reviewing some pitfalls that must be avoided when claiming functional recovery and the importance of a conceptual framework for the control of locomotion, locomotor recovery after spinal lesions, mainly in cats, is summarized. It is concluded that recovery is partly due to plastic changes within the existing spinal locomotor networks. Locomotor train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 200 publications
(231 reference statements)
1
93
0
5
Order By: Relevance
“…The onset for return of spontaneous function in both humans and animals after complete SCI could be due to the restoration of motoneuron excitability by constitutive expression of 5-HT2C receptors [11,12]. Additionally, adaptations in polysynaptic flexor reflexes involved in locomotor circuits [6,13] and synaptic rearrangements may contribute to this first phase of recovery as well [14]. The temporal differences in the spontaneous functional return onset may be due to the relatively higher metabolism of rodents.…”
Section: Spontaneous Functional Return and Recovery After Scimentioning
confidence: 99%
“…The onset for return of spontaneous function in both humans and animals after complete SCI could be due to the restoration of motoneuron excitability by constitutive expression of 5-HT2C receptors [11,12]. Additionally, adaptations in polysynaptic flexor reflexes involved in locomotor circuits [6,13] and synaptic rearrangements may contribute to this first phase of recovery as well [14]. The temporal differences in the spontaneous functional return onset may be due to the relatively higher metabolism of rodents.…”
Section: Spontaneous Functional Return and Recovery After Scimentioning
confidence: 99%
“…After a complete chronic spinal transection, the spinal locomotor CPG is undoubtedly critical for the expression of locomotion, which must involve appropriate reorganization of the spinal circuitry (Frigon and Rossignol, 2006;Rossignol, 2006). In "normal" cats (i.e., without a previous partial spinal lesion as is the case here), the expression of locomotion after a complete spinalization nor- mally takes 2-3 weeks of treadmill training without pharmacological aids (Barbeau and Rossignol, 1987).…”
Section: Reorganization Of the Spinal Locomotor Network After Partialmentioning
confidence: 99%
“…However, locomotor training greatly facilitated the recovery of locomotion after the partial spinal lesion (Lovely et al, 1986(Lovely et al, , 1990Barbeau and Rossignol, 1987;Bélanger et al, 1988Bélanger et al, , 1996Wernig and Muller, 1992;Dietz et al, 1994;de Leon et al, 1998;Van de Crommert et al, 1998;Harkema, 2001;Sullivan et al, 2002;Barbeau and Visintin, 2003;Rossignol, 2006;Plummer et al, 2007). Comparing locomotor abilities in a trained and untrained cat at the same time after the partial lesion showed that treadmill training promoted an earlier recovery of locomotion (Fig.…”
Section: Treadmill Training Promotes Spinal Plasticitymentioning
confidence: 99%
See 2 more Smart Citations